Unique Features of a Web-Based Nutrition Website for Childhood Cancer Populations: Descriptive Study - Lisa Wartenberg; Margaret Raber; Joya Chandra (JMIR Publications, 2021)
BackgroundChildren with cancer experience a myriad of nutritional challenges that impact their nutrition status during treatment and into survivorship. Growing evidence suggests that weight at diagnosis impacts cancer outcomes, but provider guidance on nutrition and diet during treatment varies. Nutrition literacy and culinary resources may help mitigate some common nutritional problems; however, many patients may face barriers to accessing in-person classes. Along with dietitian-led clinical interventions, web-based resources such as the newly updated electronic cookbook (e-cookbook) created by The University of Texas MD Anderson Cancer Center, @TheTable, may facilitate access to nutrition and culinary education during treatment and into survivorship. ObjectiveWe sought to define and describe the features and content of the @TheTable e-cookbook and compare it with analogous resources for a lay audience of patients with childhood cancer and childhood cancer survivors as well as their families. MethodsWe evaluated freely available web-based resources via a popular online search engine (ie, Google). These searches yielded three web-based resources analogous to @TheTable: the American Institute for Cancer Research's Healthy Recipes, The Children's Hospital of San Antonio's Culinary Health Education for Families Recipe for Life, and Ann Ogden Gaffney and Fred Hutchinson Cancer Research Center's Cook for Your Life. These sites were analyzed for the following: number of recipes, search functionality, child or family focus, cancer focus, specific dietary guidance, videos or other media, and miscellaneous unique features. ResultsCook for Your Life and Culinary Health Education for Families Recipe for Life were the most comparable to @TheTable with respect to cancer focus and family focus, respectively. Healthy Recipes is the least user-friendly, with few search options and no didactic videos. ConclusionsThe @TheTable e-cookbook is unique in its offering of child- and family-focused content centered on the cancer and survivorship experience.